Guiding principles of AIP reform - De Weerdt, Joachim; Duchoslav, Jan (International Food Policy Research Institute, 2022)
Malawi’s Affordable Inputs Program (AIP) currently combines an economic and a social objective, respectively: (i) increasing agricultural production; and (ii) assisting poor farming households.